2022
DOI: 10.35848/1347-4065/ac94fd
|View full text |Cite
|
Sign up to set email alerts
|

Picosecond-laser-excited photoluminescence study of AlGaN quantum wells on epitaxially laterally overgrown AlN/sapphire under selective and non-selective excitation conditions

Abstract: The radiative recombination efficiency (RRE) of AlGaN quantum wells on epitaxially laterally overgrown AlN/sapphire templates was investigated by picosecond-laser-excited photoluminescence (PL) spectroscopy under selective and non-selective excitation conditions. The PL efficiency, which was deduced by excitation-power-dependent PL measurements at low temperature (LT) and room temperature (RT), was unity at LT under both excitation conditions; However, at RT, the PL efficiency under non-selective excitation co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 32 publications
(50 reference statements)
1
0
0
Order By: Relevance
“…In addition, the AlGaN MQW structure grown on an ELO AlN/sapphire was analyzed by selective excitation time-resolved photoluminescence (TRPL). [31] It was found that at room temperature (RT) the η RRE reaches values of 60% AE 10% and, as it will be shown next, is in line with the η RRE max values extracted in this work. This agreement underlines the reliability of the Titkov method for the given case.…”
Section: Determination Of the Radiative Recombination Efficiencysupporting
confidence: 89%
“…In addition, the AlGaN MQW structure grown on an ELO AlN/sapphire was analyzed by selective excitation time-resolved photoluminescence (TRPL). [31] It was found that at room temperature (RT) the η RRE reaches values of 60% AE 10% and, as it will be shown next, is in line with the η RRE max values extracted in this work. This agreement underlines the reliability of the Titkov method for the given case.…”
Section: Determination Of the Radiative Recombination Efficiencysupporting
confidence: 89%